Differential Expression of miR-155 and miR-21 in Tumor and Stroma Cells in Diffuse Large B-Cell Lymphoma. Issue 3 (March 2015) - Munch-Petersen, Helga D.; Ralfkiaer, Ulrik; Sjö, Lene D.; Hother, Christoffer; Asmar, Fazila; Nielsen, Boye S.; Brown, Peter; Ralfkiaer, Elisabeth; Grønbæk, Kirsten
<x xml:space="preserve">Abstract</x> OncomiRs miR-21 and miR-155 have been linked to lymphomagenesis, but information on their implication in diffuse large B-cell lymphoma (DLBCL) is limited. Here, we used locked nucleic acid-based in situ hybridization (ISH) detection techniques on formalin-fixed paraffin-embedded DLBCL tissue samples to identify miR-155 and miR-21 at the cellular level in 56 patients diagnosed with DLBCL, and compared them to miR array data. miR-155 was observed in tumor cells in 19/56 (33.9%) of the samples evaluated by ISH. miR-21 was localized to the stromal compartment in 41/56 (73.2%). A subset of these, 16/56 (28.6%), also showed labeling in tumor cells. When comparing ISH-scores and miR array data, miR-155 in tumor cells, identified by ISH, was associated with miR-155 expression in miR array data (P=0.030). Equally, miR-21 expression by miR array data were highly associated with miR-21 ISH-scores in the stromal cells (P=0.002), whereas no association between miR array data and ISH of miR-21 in tumor cells was observed (P=0.673). We found no association of miR-155 and miR-21 with overall survival or germinal center B-cell–like (GCB) versus non-GCB–like subtypes of DLBCL. In conclusion, miR-ISH added to the biological interpretation of miR expression in DLBCL compared with miR array data, but miR-155 and miR-21 ISH did not add prognostic information in this series.